Hearing risk in the digital age: a systematic review on recreational audio device use among youth - Chodankar, Sandesh; Rane, Pawan (International Journal of Research in Medical Sciences, 2025)
Prolonged use of personal listening devices (PLDs) like earphones and headphones among young people has become a global concern due to the risk of hearing damage. This systematic review, which included 15 studies, found that such use is associated with early signs of auditory damage, particularly at high frequencies. While the quality of evidence varied, with some studies having a low risk of bias and others showing moderate concerns due to issues like selection and detection bias, key risk factors were consistently identified. These included the duration of listening, the volume level, and the use of earphones in noisy environments. The findings highlight the pressing need for standardised research and public health initiatives to promote safer listening practices among individuals aged 12-30.